2013
DOI: 10.1097/mrm.0b013e3283587727
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactams

Abstract: This synopsis summarizes the key chemical and bacteriological characteristics of b-lactams, penicillins, cephalosporins, carbanpenems, monobactams and others. Particular notice is given to first-generation to fifth-generation cephalosporins. This review also summarizes the main resistance mechanism to antibiotics, focusing particular attention to those conferring resistance to broad-spectrum cephalosporins by means of production of emerging cephalosporinases (extended-spectrum b-lactamases and AmpC b-lactamase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(45 citation statements)
references
References 59 publications
0
44
0
1
Order By: Relevance
“…Bacterial resistance to antibiotics has been increasing in Europe over the last few years [1][2][3]. New classes of antibiotics have not been introduced recently [4][5][6][7], and, thus, more resistances to old drugs are developing daily [8][9][10]. Recent efforts and huge investments being made in this field by big pharma companies such as GlaxoSmithKline, Merck, Pfizer and Wyeth [3][4][5]11,12] have had disappointing returns from their R&D departments, including clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial resistance to antibiotics has been increasing in Europe over the last few years [1][2][3]. New classes of antibiotics have not been introduced recently [4][5][6][7], and, thus, more resistances to old drugs are developing daily [8][9][10]. Recent efforts and huge investments being made in this field by big pharma companies such as GlaxoSmithKline, Merck, Pfizer and Wyeth [3][4][5]11,12] have had disappointing returns from their R&D departments, including clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant factor to allocate anti-infective R&D resources into other fields of investigation and thus remain highly competitive [3][4][5]13]. Considering the disappointing results on genomics and the exodus of big pharma, the problem of bacteria resistance has continued to evolve, reaching alarming dimensions [3,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such activity are -lactamase inhibition, cholesterol absorption inhibition, 3a antimicrobial, 3b-d antifungal, 4 antimalarial, 5 anti-HIV, 6 anticancer, 7 anti-inflammatory, 8 antidepressant, 9 antiviral, 10 DPP-4 inhibition 11 and anticonvulsant. 12 Additionally, lactams are very important structural motifs present in several natural products such as the penicillins 1 (Figure 1), nocardicin A (7), monobactam (8), tabtoxin (9), pseurotin A (10), dysidin (11), sintokamides A-E (12), malingamide A (13), strychnine (14), adalinine (15), corydaidine (16), caprolactin A (17), isobenganamide E (18) and bengamide K (19) ( -Lactams constitute a major class of antibiotics and contribute to more than 50% of the global antibiotics market. However, due to increasing antibacterial resistance toward -lactam antibiotics, 14 the scientific community has been forced to move its focus from four-membered lactam rings to other larger-ring lactam analogues.…”
Section: Introductionmentioning
confidence: 99%
“…12 Additionally, lactams are very important structural motifs present in several natural products such as the penicillins 1 (Figure 1), nocardicin A (7), monobactam (8), tabtoxin (9), pseurotin A (10), dysidin (11), sintokamides A-E (12), malingamide A (13), strychnine (14), adalinine (15), corydaidine (16), caprolactin A (17), isobenganamide E (18) and bengamide K (19) ( -Lactams constitute a major class of antibiotics and contribute to more than 50% of the global antibiotics market. However, due to increasing antibacterial resistance toward -lactam antibiotics, 14 the scientific community has been forced to move its focus from four-membered lactam rings to other larger-ring lactam analogues. In this context, in 1986, two independent research groups reported for the first time the synthesis of -lactam-based antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibiting the synthesis of cell wall by binding to the protein (transpeptidases) and preventing peptidoglycan cross‐linking Example ‐ Penicillins, carbapenems and cephalosporins …”
Section: Introductionmentioning
confidence: 99%